Reduction of platelet activity markers in type II hypercholesterolemic patients by a HMG-CoA-reductase inhibitor - Huhle, Günter; Abletshauser, C.; Mayer, Norman; Weidinger, G; Harenberg, Job; Heene, Dieter L. (Thrombosis research, 1999)
We have investigated the effects of a potent lipid-lowering therapy on the activity of platelets as measured ex vivo by the surface activation markers CD62 (PADGEM, P-selectin, GMP 140) and CD63 (GP53) in a double-blind, randomized, placebo-controlled study. Treatment with the HMG-CoA-reductase inhibitor fluvastatin (40 mg) significantly reduced the serum low density lipoprotein cholesterol concentration by 30% (p<0.01) and total cholesterol by 25% (p<0.01). The platelet membrane activation markers CD62 (PADGEM, P-selectin, GMP140) and 63 (GP53) significantly decreased by 22 and 13% (in terms of the relative fluorescence intensity) under the treatment with fluvastatin (p<0.05), respectively. The cholesterol-lowering effect is accompanied by a significant reduction of the platelet membrane activation markers CD62 and CD63 reflecting a reduced platelet activity that may contribute to the vasoprotective profile of fluvasatin.
Gesehen am 05.05.2022